Development of one translator's style: a corpus-based investigation of Allan Barr's style of translating Yu Hua's works - Li, Yajie; Abdullah, Muhammad Alif Redzuan; Mohd Hanafiah, Halis Azhan (Asian Economic and Social Society, 2023)
This paper examines the evolution of translator Allan Barr's style and methodology. Regarded as the primary English translator of Yu Hua's works for fifteen years, Barr's corpus is examined in order to catalogue the development of his translation style. This corpus consists of Yu Hua’s Huanghun li de Nanhai and Siyue Sanri Shijian and their translations Boy in the Twilight: Stories of Hidden China (2003) and The April 3rd Incident: Stories (2018). The mixed-methods approach was applied to analyze Barr's idiosyncrasies in translating Direct Speech (DS) presentations at different stages of his career using the revised S-type model. A quantitative analysis identified a translator’s changing preferences in translating DS. The subsequent qualitative analysis addressed the translation strategies of (Free) Direct Speech and Barr's preferred position of report clauses at different points in time. The results suggest that Barr's translation styles were more influenced by his assumptions and attitude towards the implicit target readers and then dominated his stylistic choices, leading him to be more loyal to the source text and the author in his later translation and more inclined to present the literary world of the source text with less interference and interpretation by the translator. The implications proposed that the development of the translator’s style may be due to the promotion of the author’s familiarity with the literary field of the target language, the influence of the norms of the source language in which the translator is immersed in translation practice, and his increasing knowledge of style.